PACCT: An intervention to improve communication quality and clinical trial invitations for Black and White men with prostate cancer. Issue 28 (1st October 2022) - Hamel, Lauren M.; Senft, Nicole; Kim, Seongho; Jang, Hyejeong; Manning, Mark A.; Foster, Tanina; Baidoun, Fatmeh; Carducci, Michael Anthony; Lansey, Dina; Heath, Elisabeth I.; Eggly, Susan
Abstract : 101 Background: Cancer clinical trial enrollment rates are low, with Black individuals especially underrepresented. We tested Partnering Around Cancer Clinical Trials (PACCT), a multi-level intervention designed to improve patient-physician communication and increase trial invitations among Black and White men with prostate cancer. This study reports only on PACCT Phase 1, the patient-focused intervention, because data collection for PACCT Phase 2, the physician-focused intervention, was halted by the COVID-19 pandemic. Methods: Black and White men with prostate cancer and their physicians were invited to participate. Patients were tracked <two years for trial eligibility, with eligible patients randomized to usual care or intervention. Intervention patients received a brochure that included text promoting patient-physician partnerships and a trials-focused Question Prompt List to encourage them to participate actively in clinic visits, such as by asking questions or stating concerns. Patient-physician visits with eligible patients were video-recorded. After the visits, communication (i.e., patient active participation and physician patient-centered communication) was assessed via patient self-report and observer ratings of video-recordings. Medical chart abstractions determined trial invitations. Univariable logistic mixed-effects models nesting patients within physicians tested intervention effects by race on communication and trial invitation. Results: Among 199 participants (91 Black; 108 White), 22% (n = 44; 20 Black, 24 White) became eligible for a trial and received the intervention (n = 19) or usual care (n = 25). Regarding communication, Black intervention patients reported participating more actively than those in usual care (difference = 0.41, 95% CI -0.27-1.08), while White intervention patients reported participating less actively than those in usual care (difference = -0.34, 95% CI -0.72-0.05). No differences in observer ratings of active participation or self-report or observer ratings of physician communication were found. Regarding trial invitations, findings were nonsignificant, but showed more intervention patients (74%) than usual care patients (60%) received invitations (logOR = 1.97, 95% CI -0.30 to 4.24), with Black intervention patients having higher odds of receiving invitations (80%) than White intervention patients (67%) (logOR = 3.84, 95% CI -0.92 to 8.59 vs. logOR = -0.14, 95% CI -4.61 to 4.50). Conclusions: Few patients (22%, n = 44) were eligible for a trial during PACCT Phase 1. Despite this small sample, the PACCT intervention showed promise in increasing the level of active participation among Black patients and in increasing clinical trial invitations for Black and White patients. Future research should test this intervention in a larger sample and in combination with the physician-focused intervention. Clinical trial information: NCT02906241.